Philippines-Japan Economic Partnership Agreement (PJEPA): An Initial Ex-post Review - Erlinda M. Medalla; Veredigna M. Ledda (Philippine Institute for Development Studies (PIDS), 2013)
While it is too early to undertake rigorous quantitative analysis on the impact of the Philippines-Japan Economic Partnership Agreement (PJEPA) on the Philippines, this initial ex-post study concludes that based on several key indicators the country has not suffered major adjustment costs because of the PJEPA. There is also evidence to show that the Philippines was able to secure concessions comparable to other partner countries of Japan in similar EPAs. The study echoes earlier research that indicated the short-run impact of the PJEPA on GDP would be small but the dynamic benefits could be very significant. On the whole, indicators are positive, although more could be done especially in terms of labor protection, attracting Japanese investments, and taking advantage of the cooperation elements of the agreement.
Keywords: 330; tariff; Philippines; trade; Philippines-Japan Economic Partnership Agreement (PJEPA); bilateral trade agreements